A Content and Visual Analysis of Promotional Pieces Used in a Communication Campaign for the Arkansas [Commodity] Promotion Board - Amy Hughes; Tara L Johnson; Leslie D. Edgar; Jefferson D. Miller; Casandra Cox (Journal of Applied Communications, 2016)
This study analyzed a communications campaign developed by a third-party communications group (TPCG) for a prominent commodity promotion board in Arkansas. The campaign included numerous promotional pieces targeted to three audience segments: general public, [commodity] producers, and animal agriculture producers. A systematic, content-driven assessment examined message content and visuals used in these creative pieces, comparing the actual messages with intended messages from TPCG’s original communications campaign plan. A total of 53 pieces were evaluated, and 27 different communicative themes emerged. Many of the creative pieces used in the campaign displayed multiple messages in a single piece. Celebrity endorsements of [commodity] were the most saturated theme, accounting for 21.01% of messaging in the general public creative pieces. Promotion of the [commodity] board was the most prominent theme (16.38%) in the [commodity] producer pieces. Benefits to the Arkansas economy was the most prominent theme (10.73%) in the animal agriculture creative pieces. Although TPCG predominantly achieved consistency through messages that aligned with its campaign plan, a portion of the promotional pieces across all audiences did not contain messages that were a part of the original plan. Therefore, more than one-third (38.1%) of the messages found in the creative pieces were deemed inconsistent or inconclusive. The researchers recommend utilizing a needs assessment to aid in identifying appropriate messaging, and testing those messages through standard evaluation procedures.
Keywords: Agricultural Communications; Communication Campaigns; Content and Visual Analysis; Messages; Target Audiences